Trailblazers: Stakeholder motivations for developing degree apprenticeships for the radiography profession. Issue 1 (February 2020) - Sevens, T.; Nightingale, J.
Abstract: Introduction: Employer led apprenticeship trailblazer groups develop the occupational standard and end point assessment associated with a particular job or occupation. All degree apprenticeship programmes within England must align to these and for allied health professions, this is a new concept. Exploring stakeholder motivations for being part of the trailblazer groups is essential to inform subsequent curriculum design and implementation for this new model of education. Methods: Eighteen semi-structured interviews were undertaken across the three radiography related (diagnostic, therapeutic and sonography) trailblazer groups using a pragmatic constructivist approach. Results: Strong themes emerged around professional recognition, and conflicts between being 'educated' or 'trained', and between vocational and academic components of radiography training. Even within these pioneer groups there was a lack of understanding around degree apprenticeship programmes and their potential impact upon the workforce. Whilst the benefits on recruitment and retention of staff through widening participation were acknowledged, there were concerns around apprentice pay and mentorship. Evidence of professional protectionism was uncovered, balanced by professional pride and a strong desire for team working within and between institutions. Conclusion: The study highlighted an urgent need for further research and awareness raising for employers and practitioners, prior to implementation of radiography-related degree apprenticeships. Implications for practice: This is the first evaluation of stakeholder motivations related to the development of degree apprenticeships within the allied health professions. The results and recommendations for practise will inform the imminent implementation of degree apprenticeships for the three radiography related professions, facilitating a smooth transition to apprenticeships for clinical and education departments.